PUNISHMENT FOR FOREIGN CITIZENS THAT MAKE AN ABUSE OF FREE VISIT VISA - Muhammad Arief Hamdi (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Geographically, Indonesia's territory consists of islands which have a short distance from other countries, even bordering directly with other countries. Causing the easy movement of people from one country to another. Ideally for the sake of securing the country there should be a visa to enter a country. Visas are divided into various types, one of which is a visitor visa. In applying for a visitor visa in Indonesia, the President issues a Presidential Regulation concerning visa-free visits. In Presidential Regulation No. 21 of 2016 concerning visa-free visits contained in article 3 paragraph (1) that the visa-free visa recipient is exempt from the obligation to have a visitor visa to enter Indonesian territory. And in Article 4 paragraph (1) and paragraph (2) it is stated that foreign tourists will be granted a stay permit for 30 days but cannot extend the visa-free validity period or be converted into another residence permit. This paper discusses the use of visa-free visitor visit both positive impacts and negative impacts of the visa-free visa policy. This visa-free policy issued by the President has caused an increase in the level of traffic for people entering and leaving Indonesian territory. This increase in traffic was dominated by foreigners entering and leaving Indonesian territory, this had an impact on the weak guarding of foreign workers who could not be detected due to the visa-free policy.. As well as solutions to the impacts produced by visa-free policies.